POLA PENDIDIKAN AKHLAK PADA ANAK PRAREMAJA DILINGKUNGAN KELUARGA - Budi Erliyanto (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2016)
Gutter Saling is a village located in Seluma is located in the District Seluma District, which hasmade the expansion in 2003, which split from South Bengkulu, the result of the division, is certainlygoing to change the order of life, whether from the government, in terms of revenue , culture,infrastructure, people's behavior, both in terms of children ages pre-teens, teens, adults, or even parentsthemselves, so that with the changes become Seluma, people in the Village of Salado Saling into societybegan gradually leave traditional traditions that have been there, so do not have a traditional or a newlife style, resulting in behavior or morals are not good in everyday life, which ultimately lead to nonselarasan in behavior. This study used a qualitative descriptive approach. In obtaining the data, theauthors using observation, interviews, and documentation of previous research. From the research inidiget the result that moral education is adopted by parents in the family in child preteen in the Village ofTalang Saling District of Seluma not been implemented properly by parents who have children with preteens,because there are many parents who do not implement it, most parents just rebuked him awaywithout giving punishment to his son. As well as the pattern of moral education of children of pre teen inthe family environment Village of Talang Saling District of Seluma applied by parents is lacking onceadopted by parents in the family environment, these are all visible from the percentage of parents justgive the pattern direction, that each what we do have consequences, should the parents were able to givefirmness to provide education to their children so that the pattern can be complied with and implementedin everyday life.